2014
DOI: 10.1158/2326-6066.cir-14-0052
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Vaccine Immunotherapy of Resected, Clinically Node-Negative Melanoma: Long-term Outcome and Impact of HLA Class I Antigen Expression on Overall Survival

Abstract: Associations between HLA class I antigen expression and efficacy of a melanoma vaccine (Melacine) were initially described in stage IV melanoma. Similar associations were observed in S9035, a phase III adjuvant trial evaluating Melacine for two years versus observation in patients with stage II melanoma. This report provides long-term results. The effects of treatment on relapse-free survival (RFS) and overall survival (OS) were evaluated, and pre-specified analyses investigated associations between treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the adjuvant setting, a study of allogeneic melanoma cell lysate plus the detoxified Freund’s adjuvant compared with observation in resected, clinically node negative melanoma. 38 While the overall endpoint of OS and DFS was not met (statistically insignificant increases in 5-year and 10-year survival), if the analysis was focused on patients who were HLA-A2+ and/or HLA-Cw3+, there were significant differences in both and OS at 5 years 10 years. Other studies of immunotherapy or a similar live vaccinia virus-augmented allogeneic polyvalent melanoma cell lysate did not show significant improvement in survival.…”
Section: Resultsmentioning
confidence: 98%
“…In the adjuvant setting, a study of allogeneic melanoma cell lysate plus the detoxified Freund’s adjuvant compared with observation in resected, clinically node negative melanoma. 38 While the overall endpoint of OS and DFS was not met (statistically insignificant increases in 5-year and 10-year survival), if the analysis was focused on patients who were HLA-A2+ and/or HLA-Cw3+, there were significant differences in both and OS at 5 years 10 years. Other studies of immunotherapy or a similar live vaccinia virus-augmented allogeneic polyvalent melanoma cell lysate did not show significant improvement in survival.…”
Section: Resultsmentioning
confidence: 98%
“…Several authors [ 47 49 ] have reported data to support the notion that the efficacy of vaccine immunotherapy is perhaps associated with specific HLA genotypes. Of particular interest is work by Carson, et al [ 47 ] who describe the long-term follow-up of an adjuvant melanoma cell lysate-based vaccine in the treatment of resected stage II melanoma. Specifically, the authors found an association between HLA-A2 and improved recurrence-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In other tumor types, expression levels of PD‐L1 have been linked to OS, DFS, treatment efficacy, and treatment outcomes 7‐9 . CD8 + TILs have been associated with outcomes, 10,11 and HLA class 1 expression has been linked to treatment efficacy, relapse‐free survival, and OS 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] CD8 + TILs have been associated with outcomes, 10,11 and HLA class 1 expression has been linked to treatment efficacy, relapse-free survival, and OS. 12,13 Nivolumab is a genetically engineered, fully human IgG4 mAb targeted at human PD-1. 14 A multicenter, open-label, uncontrolled, phase II study evaluated the efficacy and safety of nivolumab in 65 Japanese patients with advanced esophageal cancer refractory or intolerant to standard chemotherapy.…”
Section: Introductionmentioning
confidence: 99%